Implementation of Node.js and JWT Security for a Web-Based Elementary School Management Information System - Kurnia, Rizal; Huizen, Lenny Margaretta (Jurnal Transformatika, 2026)
The need for an efficient and secure school management system presents a major challenge for educational institutions. A backend system for elementary school management in Semarang City was developed using Node.js to address this need, yet its performance has not been quantitatively measured. This research aims to analyze the performance and security of the backend system, focusing on three main aspects: functionality, security, and performance under load. The research method used is quantitative analysis through functional and non-functional testing. Functional testing was conducted to validate all API endpoints, security testing to verify the JWT-based authentication mechanism, while non-functional testing utilized load testing to measure response times and error rates under simulated user load. The test results showed success in all aspects: API functionality testing achieved a 100% valid status, the security system proved effective in blocking unauthorized access via the JWT mechanism, and a load test with 50 simultaneous users demonstrated highly optimal performance. Specifically, the system recorded an average response time of 7 ms, a throughput of 40.59 requests/second, with a 0% error rate. These findings quantitatively prove that the backend system for the Semarang City elementary school management possesses reliable performance, complete functionality, and adequate security, making it ready for implementation.